2022
DOI: 10.3390/heritage5030079
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Enhancement of the Pietrabbondante Archaeological Site between History, Geology and Emerging Crowd-Based Digital Technologies

Abstract: Attention to the condition assessment and conservation of cultural heritage is increasing due to growing sensitivity to the preservation of the built and natural environment and awareness of the risks associated with natural hazards. In this context, a comprehensive approach to the conservation and valorization of cultural heritage requires the combined action of different skills to achieve reliable assessment of the conditions of valuable assets and sites based on qualitative and quantitative indicators. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…This approach was most frequently applied to assess vulnerability (23%) and risk (24%) (Figure 3), which can be related to the necessity of assessing both the physical and social aspects to properly estimate landslide risk. The combination of different questionnaire survey techniques and geomorphological knowledge [65,66], geomorphological and geomatic information with crowdsourcing to engage the general public for cultural heritage preservation [67], and dendrogeomorphological and traditional monitoring techniques [68] are examples of the necessity to integrate several scientific disciplines to assess landslide threats on cultural heritage sites.…”
Section: Publications By Year Study Scope and Approach-based Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was most frequently applied to assess vulnerability (23%) and risk (24%) (Figure 3), which can be related to the necessity of assessing both the physical and social aspects to properly estimate landslide risk. The combination of different questionnaire survey techniques and geomorphological knowledge [65,66], geomorphological and geomatic information with crowdsourcing to engage the general public for cultural heritage preservation [67], and dendrogeomorphological and traditional monitoring techniques [68] are examples of the necessity to integrate several scientific disciplines to assess landslide threats on cultural heritage sites.…”
Section: Publications By Year Study Scope and Approach-based Categoriesmentioning
confidence: 99%
“…Combining survey techniques and crowdsourcing, Marra et al [67] showed the potential of engaging the public and managers of cultural heritage sites at the Samnite complex of Pietrabbondante (Molise, Italy). The proposal of the SUNDAE 1.0 catalog integrates national document databases, geological and geomorphological information, and cloudbased photos and videos collected by the public that can be used to update virtual models of the sites to assess the heritage's state of conservation while engaging the public on the preservation efforts.…”
Section: Publications By Year Study Scope and Approach-based Categoriesmentioning
confidence: 99%
“…The topic of 3D recording and digitalization of tangible cultural heritage is covered in a number of literary works (Giulio et al, 2018;Nocerino et al, 2018;Chen et al, 2018, Hussein andIsmaeel, 2020;Marra et al, 2022;Bastem and Cekmis, 2022). Generally speaking, they are taking into consideration buildings (Brumana et al, 2018), monuments (Apollonio et al, 2017;Adamopoulos and Rinaudo, 2021), old city centers (Cecchini, 2019;Ramírez Eudave and Ferreira, 2021 ), and even rural places (Merchán et al, 2021, Boboc et al, 2022.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, the use of alternative measurement techniques for one-shot measurements is recommended. The authors propose a thermography-based technique to evaluate the conservation state of the archaeological discovery so to schedule the next restoration activity, [8], [9]. Thermography is a diagnostic technique used in several application fields such as the environmental one, [10], [11], biomedical one [12] and industrial one.…”
Section: Introductionmentioning
confidence: 99%